(1642) Genetic Algorithms and programming Introducing the Concept and Domain of Applications الخوارزميات الجينية والبرمجة: مقدمة عن المفهوم ومجال التطبيقات - ElKafrawy, M.; Ismail, I.A. (معهد التخطيط القومى, 2022)
On these notes we introduce the most important modern methods that are in use today. These notes comprise some applications to the genetic algorithms together with the written programs for each of these applications.